PHYSICAL STATE AND ATTITUDE TOWARDS THE STUDY. CASE OF STUDENTS FROM THE NATIONAL TECHNOLOGICAL UNIVERSITY OF LIMA SUR - Villavicencio Torres, Luis Max (2020)
Objective: To determine the physical state and general attitude towards study in first and second cycle students of five study careers at the National Technological University of Lima Sur. Materials and method: The research has a quantitative approach, a non-experimental, descriptive and correlational design. This study was carried out by 428 first and second cycle students from five degree courses at a national technological university in Lima Sur. The questionnaire used for this sample is Study Habits and Techniques - CHTE, which consists of 16 items. Results: The Business Administration career presents the highest averages of physical condition and general attitude towards studying. At university, the correlation between physical condition and general attitude towards studying is directly proportional and significant (R = 0.219; p <0.01). Conclusions: There is a significant relationship between physical condition and general attitude towards study in first and second cycle students of five careers at the Universidad Nacional Technologic Lima Sur.